2008
DOI: 10.1111/j.1439-0426.2001.00283.x
|View full text |Cite
|
Sign up to set email alerts
|

By-catch and discarding practices in five Algarve (southern Portugal) métiers

Abstract: The catches and discards of trawlers, seiners and trammel netters were studied in the Algarve (southern Portugal) using observers onboard commercial ®shing vessels. Species diversity was high, with 236 species recorded as occasionally, frequently or regularly discarded. Mean discard rates per trip were 0.13, 0.20, 0.27, 0.62 and 0.70, respectively, for trammel nets, demersal purse seines, pelagic purse seines, ®sh trawls and crustacean trawls, with high variability in terms of discard volume and discard rate. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
62
1
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(68 citation statements)
references
References 12 publications
3
62
1
1
Order By: Relevance
“…Stergiou et al (2006) studied the trammel net catch species composition in southern European waters and concluded that both season and depth strongly affected catch species composition and that trammel net fishing occurs in 'hot spots', which represent essential habitats of the life history of the targeted and associated species. In Portuguese coastal areas some studies on trammel net fisheries and their impacts on sea grounds have been previously conducted, but all of them along the southern coast of Portugal's mainland (Borges et al, 2001;Erzini et al, 1997Erzini et al, , 2002Gonç alves et al, 2007Gonç alves et al, , 2008a.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stergiou et al (2006) studied the trammel net catch species composition in southern European waters and concluded that both season and depth strongly affected catch species composition and that trammel net fishing occurs in 'hot spots', which represent essential habitats of the life history of the targeted and associated species. In Portuguese coastal areas some studies on trammel net fisheries and their impacts on sea grounds have been previously conducted, but all of them along the southern coast of Portugal's mainland (Borges et al, 2001;Erzini et al, 1997Erzini et al, , 2002Gonç alves et al, 2007Gonç alves et al, , 2008a.…”
Section: Introductionmentioning
confidence: 99%
“…This fishing gear is included in various métiers which are characterized by different combinations of mesh sizes, fishing grounds, fishing time, season, markets and consequently target species (e.g. Borges et al, 2001;Stergiou et al, 2006). Thus, trammel net catches along Portuguese coast are composed of a wide range of species, some of them with recognized or expected management problems (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…According to the analysis performed by Borges et al (2001), O. vulgaris is a species frequently discarded. Nevertheless, it does not appear among those that are discarded in any significant quantities in the same study and in a similar analysis by Erzini et al (2002).…”
Section: Discussionmentioning
confidence: 99%
“…Also, the physical disturbance of the sediment by trawl nets could expose endobenthic organisms which can then be predated by carnivores (Jenkins et al, 2004). However, the effects on ecosystem structure and function (biodiversity, community structure, trophic links) of returning biomass directly to the ecosystem though discarding are not so well known (Dayton et al, 1995;Jennings & Kaiser, 1998;Lindeboom & de Groot, 1998;Hall, 1999;Collie et al, 2000;Kaiser & de Groot, 2000;Borges et al, 2001;Erzini et al, 2002). The effects of discarding on the stability of trophic webs may have negative consequences for commercial stocks due to the disruption of species interactions and cascading effects throughout the trophic chains (Monteiro et al, 2001).…”
Section: On the Impact Of Fishing And Discards In The Ecosystemmentioning
confidence: 95%
“…Knowledge of the impacts of bycatch and discarding at the community and ecosystem levels becomes increasingly necessary in the context of the multispecies and ecosystem-based approaches to fisheries management (Borges et al, 2001).…”
Section: On the Impact Of Fishing And Discards In The Ecosystemmentioning
confidence: 99%